3-bromopyruvate, butyrate, monocarboxylate transporters, warburg effect - Queirós, Odília (2012)
The authors are deeply grateful to Professor André Goffeau (Université Catholique de Louvain-la-Neuve, Belgium) for his contagious vision, valuable discussions at the Conference on 3-BP held in Brussels, 29 October–2 November, 2011 and critical reviewing of the manuscript. The authors also thank Dr. Rita Reis for her technical support in microscopy and image analysis.